Fiscal redistribution, social welfare and income inequality: 'doing more' or 'more to do'?. Issue 21 (3rd May 2022) - Coady, David; D'Angelo, Devin; Evans, Brooks
ABSTRACT: This paper embeds the analysis of fiscal redistribution (FR) within the standard social welfare framework (SWF), which lends itself to a transparent and practical evaluation of the determinants of FR. Differences in FR are decomposed into differences in fiscal effort (the magnitude of redistributive transfers) and in fiscal progressivity (the distribution of net transfers across different income groups). Progressivity is further decomposed into targeting performance (the share of net transfers accruing to lower-income groups) and targeting returns (the social returns to targeting due to differences in the initial income inequality). This highlights the possibility that countries with the exact same redistributive effort (fiscal effort and targeting performance) can have very different levels of FR simply because they have very different levels of initial income inequality. High levels of FR in a country may therefore reflect that it has 'more to do' (high initial inequality) as opposed to it 'doing more'. To illustrate, the paper decomposes differences in FR across 28 EU countries to isolate the importance of initial income inequality in explaining these differences. It also shows how the SWF can be straightforwardly used to test for the existence of the Paradox of Redistribution .